Transport Phenomena in Films and Coatings Including Their Mathematical Modeling - García, María Alejandra (2016)
In the present chapter, two examples related to transport phenomena in films and coatings are discussed. One of them represents the heat and mass transfer process in fried foods that were covered with an edible coating based on methylcellulose (MC). This is an alternative to reduce oil uptake (OU) in fried foods due to its lipid-barrier properties. The following aspects are discussed: (1) mathematical modeling of heat and moisture transfer during the deep-fat frying of food, (2) experimental validation of the mathematical model with regard to the temperature profiles and the water losses from the food product, (3) analysis of the relationship between the OU measurements and microstructural changes developed, and (4) performance of applying an edible coating based on MC on a food model dough system. The mathematical model of the frying process based on the numerical solution of the heat and mass transfer differential equations under unsteady-state conditions was proposed and solved. It allows simulating satisfactorily the experimental data of temperature and water content during the different frying stages. OU was also linearly correlated with water loss at the initial frying stage. A simple equation for OU as a function of frying times was proposed, considering the microstructural changes developed during the frying process. The presence of MC coating reduced the OU, modifying the wetting properties and also becoming a mechanical barrier to the oil. The second example represents the mathematical modeling of potassium sorbate release from a starch biodegradable active film to a model food system represented by a gel in contact with the active film. Mass transfer partial differential equations in nonstationary conditions were numerically solved using the finite element method. The model assumes a constant initial mass of antimicrobial in the active film that diffuses through the film penetrating in the food system. The numerical solution allowed the determination of the diffusion coefficients of the antimicrobial agent in both, the film and the gel. Concentration profiles were simulated to predict the time period in which the antimicrobial concentration can be maintained above the critical inhibitory concentration in the packaged food. Experimental data of sorbate diffusion from active films and from a liquid solution to the semisolid medium were compared with the predicted concentration profiles. The model allows the simulation of nonstationary diffusion of different additives incorporated to polymeric matrixes, taking into account the preservative concentration in the film and the dimensions of the semisolid food system.